Thermally stable and high reflectivity Al-doped silver thin films deposited by magnetron sputtering. (7th March 2018) - Loka, Chadrasekhar; Lee, Kwang; Joo, Sin Yong; Lee, Kee-Sun
Abstract: Thermally stable, high reflectance thin film coatings are indispensable in optoelectronic devices, especially as a potential back reflector for LEDs and solar cells. The silver has the drawback of agglomerating easily and poor thermal stability, which is limiting its application as a highly reflective coating in various optoelectronic applications. In this study, improved thermal stability by modification of the Ag film into an Ag/Al-doped Ag structure has been confirmed. In this paper, the surface morphology, optical reflectance, and thermal stability of the Ag/Al-doped Ag are investigated. The Ag/Al-doped Ag/sapphire films showed excellent thermal stability after annealing the films at 523 K with the highest reflectance about ∼86% as compared to the pure Ag films. The grain growth analysis results revealed that the Al-doping is effective to restrain the severe grain growth of silver films. The Auger electron spectroscopy results revealed that the outer diffusion of aluminum and the formation of Al-O bond at the outermost silver layer which is beneficial to retard the Ag grain growth.